Pengaruh Transformational Leadership dan Quality of Work Life terhadap Organizational Citizenship Behavior melalui Organizational Commitment sebagai Variabel Mediasi pada Karyawan Food & Beverage Generasi Z Kota Semarang - Aditya Dwi Kurniawan; Desti Ranihusna (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of transformational leadership and quality of work life on organizational citizenship behavior (OCB), with organizational commitment as a mediator among Generation Z employees in the food and beverage sector in Semarang City. Using a quantitative approach and purposive sampling, data were collected from 195 respondents and analyzed using SmartPLS4. Results show that transformational leadership and organizational commitment significantly affect OCB, whereas quality of work life has no direct effect. Organizational commitment acts as partial and full mediation. These findings highlight the importance of transformational leadership and commitment in promoting sustainable employee behavior. Keywords: Transformational Leadership; Quality of Work Life; Organizational Commitment; Organizational Citizenship Behavior; Generation Z Employees; Food and Beverage Industry; Semarang City